FAKTOR YANG BERHUBUNGAN DENGAN STRES KERJA PADA PENYELAM DI PT. X - Irkhami, Faris Lazwar (Universitas Airlangga, 2015)
ABSTRACTStress can be perceived as a response to threats situations (either physical or psychological) caused by individual inabilityÂ to overcome existing threats within his/her environment. Job stress is the result of interaction between an individual (i.e. a worker) and his/her occupation. The objective of this study to identify the factor affecting tojob stress by the divers at PT. X. This study applied cross-sectional design conducted by observing the divers at PT. X. The population of this study was all divers working at PT. X. Data was analyzed by Spearman Correlation Test, Pearson Correlation Test, and Chi-square Test. The results of this study is strong correlation between personality type and job stress (as indicated by correlation coefficient 0.645). The diversâ age (correlation coefficient -0.283), educational level (correlation coefficient -0.220), years of service/experience (correlation coefficient -0.158), length of diving session (correlation coefficient 0.083), and threats of marine animal attack (correlation coefficient 0.156) had lower correlation with job stress. While the divers residence might also affect their job stress (as indicated by correlation coefficient 0.539).Keywords: job stress, diver